G-Invariant Deformations of Almost-Coupling Poisson Structures - Vallejo, J.A.; Vorobiev, Y. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
On a foliated manifold equipped with an action of a compact Lie group G, we study a class of almost-coupling Poisson and Dirac structures, in the context of deformation theory and the method of averaging.